Chrysanthemum sporopollenin: A novel vaccine delivery system for nasal mucosal immunity - Liu, Jun; Yan, Xiao-Dan; Li, Xian-Qiang; Du, Yu-Hao; Zhu, Li-Li; Ye, Tian-Tian; Cao, Ze-Ying; Dong, Zhe-Wen; Li, Shu-Tao; Xu, Xue; Bai, Wei; Li, Dan; et al. (Frontiers in Immunology, 2023)
Mucosal immunization was an effective defender against pathogens. Nasal vaccines could activate both systemic and mucosal immunity to trigger protective immune responses. However, due to the weak immunogenicity of nasal vaccines and the lack of appropriate antigen carriers, very few nasal vaccines have been clinically approved for human use, which was a major barrier to the development of nasal vaccines. Plant-derived adjuvants were promising candidates for vaccine delivery systems due to their relatively safe immunogenic properties. In particular, the distinctive structure of pollen was beneficial to antigen stability and retention in the nasal mucosa. Herein, a novel wild-type chrysanthemum sporopollenin vaccine delivery system loaded with a W/O/W emulsion containing squalane and protein antigen was fabricated. The unique internal cavities and the rigid external walls within the sporopollenin skeleton construction could preserve and stabilize the inner proteins. The external morphological characteristics were suitable for nasal mucosal administration, with high adhesion and retention. Secretory IgA antibodies in the nasal mucosa can be induced by the W/O/W emulsion with the chrysanthemum sporopollenin vaccine delivery system. Moreover, the nasal adjuvants produce a stronger humoral response (IgA and IgG) compared to squalene emulsion adjuvant. Mucosal adjuvant benefited primarily from prolongation of antigens in the nasal cavity, improvement of antigen penetration in the submucosa, and promotion of T cells in CD8+ nasal mucosal associated lymphoid tissue. Based on effective delivering both the adjuvant and the antigen, the increase of protein antigen stability and the realization of mucosal retention, the chrysanthemum sporopollenin vaccine delivery system has the potential to be a promising adjuvant platform, providing a novel idea for the fabrication of protein-mucosal delivery vaccine.